2013
DOI: 10.1088/1367-2630/15/4/045026
|View full text |Cite
|
Sign up to set email alerts
|

Thermorheology of living cells—impact of temperature variations on cell mechanics

Abstract: Upon temperature changes, we observe a systematic shift of creep compliance curves J (t) for single living breast epithelial cells. We use a dual-beam laser trap (optical stretcher) to induce temperature jumps within milliseconds, while simultaneously measuring the mechanical response of whole cells to optical force. The cellular mechanical response was found to differ between sudden temperature changes compared to slow, long-term changes implying adaptation of cytoskeletal structure. Interpreting optically in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(78 citation statements)
references
References 47 publications
(70 reference statements)
4
74
0
Order By: Relevance
“…(2)) on temperature is reported in Fig. 4(a), showing that higher values of Var are observed at higher temperatures, in agreement with results recently reported in literature [10,11]. In order to evaluate the significance of the differences, Mann-Whitney U-test was performed as the population was non-normal according to the Kolmogorov-Smirnov test.…”
Section: Optical Deformation and Passage Through Constrictionssupporting
confidence: 88%
See 2 more Smart Citations
“…(2)) on temperature is reported in Fig. 4(a), showing that higher values of Var are observed at higher temperatures, in agreement with results recently reported in literature [10,11]. In order to evaluate the significance of the differences, Mann-Whitney U-test was performed as the population was non-normal according to the Kolmogorov-Smirnov test.…”
Section: Optical Deformation and Passage Through Constrictionssupporting
confidence: 88%
“…The obtained results on optical deformability showed a statistically significant difference (p < 10 −3 ) between all the five temperatures. As known from literature [10,21,22], laser power can induce a sudden increase of the cell temperature, making it difficult to compare the deformation values obtained at different optical power levels. As in our case the same optical power is applied to all OS measurements, we expect an increase of about 30°C in the irradiated region for all the samples, provided that absorption coefficient changes due to the different temperatures are negligible.…”
Section: Optical Deformation and Passage Through Constrictionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the fact that the OS, operated at a wavelength of 1064 nm, might introduce additional heating effects that can impact cell rheology (34,38,39), we employed a MMM to confirm the impact of changes to suspended cell mechanical properties free from heating artifacts (see Materials and Methods). In this setup, cells were advected sequentially through a long microchannel with many constrictions smaller than the cell diameter using driving pressures within physiological range (50 mbar) (Fig.…”
Section: Cell Stiffening Correlates With Longer Advection Time Througmentioning
confidence: 99%
“…Interestingly, cells became effectively stiffer with blebbistatin treatment, which is in contrast to measurements by AFM and the dual optical trap [43]. Recently, it was shown that next to the optical deformation of a cell, there is also a significant thermal effect on the sample that allows to induce rapid changes in temperature [44]. Exploiting this thermal effect, the optical stretcher setup therefore allows a new class of experiments called 'thermorheology' that go beyond purely mechanical deformation.…”
Section: Optical Stretchermentioning
confidence: 99%